2017
DOI: 10.1073/pnas.1700340114
|View full text |Cite
|
Sign up to set email alerts
|

Role of vascular normalization in benefit from metronomic chemotherapy

Abstract: Metronomic dosing of chemotherapy-defined as frequent administration at lower doses-has been shown to be more efficacious than maximum tolerated dose treatment in preclinical studies, and is currently being tested in the clinic. Although multiple mechanisms of benefit from metronomic chemotherapy have been proposed, how these mechanisms are related to one another and which one is dominant for a given tumor-drug combination is not known. To this end, we have developed a mathematical model that incorporates vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 58 publications
11
119
0
1
Order By: Relevance
“…This indicated that metronomic chemotherapy modulated antitumor immunity in tumor microenvironment. The similar finding from recent report also demonstrated that metronomic chemotherapy can normalize tumor vasculature to increase tumor perfusion and oxygen pressure and improved perfusion alleviates hypoxia, which reprograms the immunosuppressive tumor microenvironment toward immunostimulation [35]. Based on our finding, this immune-competent orthotopic HCC model can reflect the truest experimental results and mimic the clinical condition.…”
Section: Celecoxib Improves Chemotherapy In Hccsupporting
confidence: 88%
See 1 more Smart Citation
“…This indicated that metronomic chemotherapy modulated antitumor immunity in tumor microenvironment. The similar finding from recent report also demonstrated that metronomic chemotherapy can normalize tumor vasculature to increase tumor perfusion and oxygen pressure and improved perfusion alleviates hypoxia, which reprograms the immunosuppressive tumor microenvironment toward immunostimulation [35]. Based on our finding, this immune-competent orthotopic HCC model can reflect the truest experimental results and mimic the clinical condition.…”
Section: Celecoxib Improves Chemotherapy In Hccsupporting
confidence: 88%
“…On the contrary, chemotherapy reduced CD44 and CD133 expression in this rat orthotopic hepatoma. A similar finding from other research indicated metronomic chemotherapy increased the killing of CSCs via improved immune response . However, celecoxib can suppress hepatic cancer stemness and activate antitumor activity to enhance chemosensitivity in liver cancer.…”
Section: Discussionsupporting
confidence: 78%
“…Certain molecularly targeted agents, such as the anti-HER2 antibody trastuzumab, and metronomic chemotherapy can also induce vascular normalization via upregulation of thrombospondin expression 28,116,117 . Moreover, endocrine therapy for hormone-dependent tumours can also reduce VEGF levels and normalize tumour vessels 118 .…”
Section: Perspectivesmentioning
confidence: 99%
“…Apart from anti-angiogenic treatment, tumor perfusion and tumor vessel function can be significantly improved using metronomic chemotherapy [26], in which lower doses of the chemotherapeutic agent are administered more frequently. In fact, metronomic administration is currently being tested in clinical trials, as it was shown to be more efficacious than maximum tolerated dose treatment in preclinical studies [27].…”
Section: Strategies To Improve Drug Deliverymentioning
confidence: 99%
“…Thus, vascular normalization restores tumor perfusion by fortifying the vessel wall and the vascular network structure, which also decreases interstitial fluid pressure due to the reduced amount of fluid leaking from the vessels. Anti-angiogenic treatments worked well in preclinical models but failed in clinical trials [24], and combinatorial approaches have been employed extensively both in preclinical and clinical studies with varying degrees of success [9,25] whereby the anti-angiogenic drug aims to normalize and not destroy the vessels and it is combined with chemotherapy to eradicate the tumor.Apart from anti-angiogenic treatment, tumor perfusion and tumor vessel function can be significantly improved using metronomic chemotherapy [26], in which lower doses of the chemotherapeutic agent are administered more frequently. In fact, metronomic administration is currently being tested in clinical trials, as it was shown to be more efficacious than maximum tolerated dose treatment in preclinical studies [27].…”
mentioning
confidence: 99%